The Use of Fuzzy Analytic Hierarchy Process (Fuzzy AHP) for Inspection Mechanisms Selection towards Automated Inspection System Development: A Case Study - Purushothaman, Kumaraendran; Ahmad, Rosmaini (Journal of Technology Management and Business, 2022)
This paper presents an application of Fuzzy Analytic Hierarchy Process (Fuzzy AHP) method for inspection mechanisms selection towards automated inspection system development. A case study from the adhesive tape-based manufacturing industry was used to show the applicability of the method. The Fuzzy AHP method applied in this paper consists of four steps; hierarchy structure development, criteria weighting, alternative weighting and final score of the alternative. The four criteria (cost, reliability, durability and minimal lagging) and three alternatives (pressure strips, profiling pressure and image) are firstly defined in the development of the hierarchy structure. Based on the evaluation process of criteria and alternative weighting, the final score of each alternative is obtained. The final result shows that the alternative of the image gives the highest score at 0.706, followed by profiling pressure and pressure strips at 0.645 and 0.081, respectively. Therefore, the alternative of the image is highly recommended to be used as the inspection mechanism for automated inspection system development.